Resilience of milled rice sellers in Tacloban City amid typhoon disruptions - Bagobe, Cyrus Faye Lynn O.; Bianes, Justine T.; Francisco, Trisha E.
Rice is a fundamental staple in Filipino's daily diet, rendering the security of its supply chain essential to food stability. In Tacloban City, an area prone to super typhoons, disruptions caused by such natural hazards pose significant threats to rice distribution and retail operations. While prior research has explored the impact of typhoons on agricultural supply chains broadly, there remains a limited focus on the experiences of milled rice sellers who are the key actors in the post-harvest supply process. This study addresses this gap by examining the resilience and adaptive strategies employed by milled rice sellers in Tacloban City in response to typhoon-induced disruptions. Utilizing a qualitative approach, data were gathered through semi-structured interviews with purposively selected participants. Narrative analysis was employed to capture the sellers' lived experiences, while inductive thematic analysis identified patterns and themes associated with their coping and resilience mechanisms. Findings indicate that all participants experienced operational disruptions due to typhoons, particularly in rice acquisition, distribution, and retailing. Key challenges included infrastructure damage, increased operational costs, and reduced supply due to diminished supplier availability. While most respondents anticipated post-typhoon price increases, some attributed price fluctuations to broader economic factors. Furthermore, the study highlights three dimensions of resilience among rice sellers: adaptive capacity (engagement in alternative sourcing and processes), restorative capacity (recovery through facility repair and improved stock management), and absorptive capacity (implementation of lessons learned from previous typhoons). These insights underscore the urgent need for strengthened disaster preparedness frameworks and support mechanisms to enhance the resilience of rice sellers in vulnerable urban regions.